Hrólfs saga kraka: A Tragedy, Comedy, History, Pastoral, Pastoral-Comical, Historical-Pastoral, Tragical-Historical, Tragical-Comical-Historical-Pastoral . Romance - Denzin, Johanna (Cornell University Library, 2008)
Page range: 207-230